The new rules of marketing and PR how to use news releases, blogs, podcasting, viral marketing & online media to reach buyers directly - Scott, David Meerman (John Wiley & Sons, 2007)
"The New Rules of Marketing and PR shows you how to leverage the potential that Web-based communication offers large and small companies, nonprofits, entrepreneurs, political organizations, consultants, even rock bands and churches. Finally, you can speak directly to customers and buyers, establishing a personal link with those who make your business work. You can reach niche buyers with targeted messages that cost a fraction of your big-budget advertising campaign. Rather than bombard them with advertising they'll likely ignore, you can focus on getting the right message to the right people at the right time."--Jacket
Includes bibliographical references and index. - Print version record
Keywords: Internet marketing; Public relations; Public Relations; Marketing sur Internet; Relations publiques; public relations; BUSINESS & ECONOMICS; Marketing; Telemarketing; BUSINESS & ECONOMICS; Marketing; Multilevel; BUSINESS & ECONOMICS; Mail Order; BUSINESS & ECONOMICS; Marketing; Direct; BUSINESS & ECONOMICS; E-Commerce; Internet Marketing